Kemampuan Pemecahan Masalah Matematika Siswa dengan Gaya Kognitif Field Dependent dan Field Independent - Hasdi Hasdi; Manuharawati Manuharawati; Raden Sulaiman (LP. Ma'arif Janggan Magetan, 2024)
This study is a qualitative descriptive research with the aim of describing students' mathematical problem solving with Field Dependent (FD) and Field Independent (FI) cognitive styles. The subjects of this study consisted of 2 grade VIII junior high school students with Field Dependent (FD) and Field Independent (FI) cognitive styles. The selection of both subjects also considers equal mathematical ability, equal gender, communicative, and willing. The data is analyzed based on the polya problem-solving stages, namely understanding the problem, planning the solution, implementing the solution plan, and rechecking. The results of the study showed that the mathematical problem solving of the two students in solving the problem was relatively the same. At the stage of understanding the problem, both students are able to write down what is known and what is asked in the question, but FD tends to write the same thing about what is in the problem while FI uses his own language. At the stage of planning the settlement of FD fans, FIs are equally able to make strategies or steps to solve the problem. At the stage of implementing the settlement plan, FD and FI are both able to carry out the strategy that has been prepared previously. FI is confident that the answer obtained is correct. However, it is different from FD where he is not sure or doubtful about the answer because in the process of solving the problem there are errors caused by lack of thoroughness. At the stage of re-checking, the FI confidently said that he had re-examined carefully and was confident in the answers obtained. In contrast to FD who said he had double-checked but was not sure whether the answer obtained was correct or not.